2013
DOI: 10.1063/1.4800321
|View full text |Cite
|
Sign up to set email alerts
|

Jet meandering by a foil pitching in quiescent fluid

Abstract: The flow produced by a rigid symmetric NACA0015 airfoil purely pitching at a fixed location in quiescent fluid (the limiting case of infinite Strouhal number) is studied using visualizations and particle image velocimetry. A weak jet is generated whose inclination changes continually with time. This meandering is observed to be random and independent of the initial conditions, over a wide range of pitching parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
(17 reference statements)
1
25
0
Order By: Relevance
“…The flow from the rigid foil is discussed in detail by Shinde & Arakeri (2013). In dramatic contrast, for the same pitching conditions, attaching a chordwise flexible flap to the foil creates a coherent, undulating jet composed of vortices in a 'reverse Bénard-Kármán vortex street' aligned along the centreline (figure 2b).…”
Section: Flow Structurementioning
confidence: 97%
See 2 more Smart Citations
“…The flow from the rigid foil is discussed in detail by Shinde & Arakeri (2013). In dramatic contrast, for the same pitching conditions, attaching a chordwise flexible flap to the foil creates a coherent, undulating jet composed of vortices in a 'reverse Bénard-Kármán vortex street' aligned along the centreline (figure 2b).…”
Section: Flow Structurementioning
confidence: 97%
“…increase in U ∞ ). For the limiting condition of St tending to infinity (U ∞ = 0), non-symmetric jets are observed for heaving and pitching rigid foils (Freymuth 1990;Gustafson et al 1992;Lai & Platzer 2001); the jets meander across the centreline either quasiperiodically (Heathcote & Gursul 2007, for purely heaving motion), or continually and randomly (Shinde & Arakeri 2013, for purely pitching motion). Marais et al (2012) recently showed that chordwise flexibility increases separation between successively shed vortices and prevents jet inclination up to St = 1.2 compared with the value of St 0.4 for rigid foils.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As there is no free stream in the present experiments, it needs to be emphasized that the jet flow is entirely due to the flapping motion of the flexible foil. In the absence of free-stream flow, the jet generated by the flapping foil has the tendency to switch direction [20,22]. Shinde & Arakeri [29] have identified the two underlying mechanisms for suppressing the jet meandering and generating the coherent reverse Bénard-Kármán vortex street and the unidirectional thrust along the centreline: first, appropriate spatial and temporal shedding of the vortices from the flap tip, and, second, convection of the vortices away from the place of shedding.…”
Section: The Flowmentioning
confidence: 99%
“…They also observed that the switching period increased with increased foil stiffness. In a related study, Shinde & Arakeri (2013) observed the long-time behaviour of the meandering jet to be random in time and not dependent on initial conditions. They opined that the leading-edge vortices observed in Heathcote & Gursul's experiments could account for the differing results.…”
Section: Similarities To Aerofoil Propulsionmentioning
confidence: 94%